PENYULUHAN TERHADAP URGENSI KESADARAN HUKUM PINJAMAN ONLINE ILEGAL BAGI MASYARAKAT DESA BETUNG LAMPUNG SELATAN - Shafira, Maya; Achmad, Deni; Farid, Muhammad; Meidiantama, Refi; Rifai, Akhmad (Nemui Nyimah, 2025)
The rise in illegal online loan cases (pinjol) in Indonesia, especially in rural areas, is a serious problem that requires special attention. The lack of digital and financial literacy makes rural communities, including in South Lampung, vulnerable to being trapped in illegal lending practices that are detrimental. This counseling activity aims to increase public awareness of the dangers and impacts of illegal pinjol and provide an understanding of how to recognize and avoid them. The method used is an educational approach through seminars, interactive discussions, and the distribution of educational materials. The results of the emergency counseling activity on illegal online loans for rural communities in South Lampung showed an increase in participants' understanding of the characteristics of illegal loans and preventive steps that can be taken. It is hoped that this activity can be the first step in forming a society that is more critical and alert to unofficial digital financial practices.